What Kind of Economic Citizen? A Response - Ryan Crowley; Kathy Swan (MDPI AG, 2018)
In our previous work (Crowley & Swan, 2018), we extended the three citizenship categories (personally responsible, participatory, justice-oriented) created by Westheimer and Kahne into the realm of economic citizenship. In doing so, we added a fourth citizenship archetype: the discerning economic citizen. In a comment on our original article, Cameron (2018) suggested that the discerning economic citizen is not a distinct archetype, but rather a foundational aspect of all elements of economic citizenship. Herein, we provide greater foundation for our decision to separate out the discerning economic citizen.